Identification of Wolbachia strains in mosquito disease vectors. - Jewelna Osei-Poku; Calvin Han; Charles M Mbogo; Francis M Jiggins (PLoS ONE)
Wolbachia bacteria are common endosymbionts of insects, and some strains are known to protect their hosts against RNA viruses and other parasites. This has led to the suggestion that releasing Wolbachia-infected mosquitoes could prevent the transmission of arboviruses and other human parasites. We have identified Wolbachia in Kenyan populations of the yellow fever vector Aedes bromeliae and its relative Aedes metallicus, and in Mansonia uniformis and Mansonia africana, which are vectors of lymphatic filariasis. These Wolbachia strains cluster together on the bacterial phylogeny, and belong to bacterial clades that have recombined with other unrelated strains. These new Wolbachia strains may be affecting disease transmission rates of infected mosquito species, and could be transferred into other mosquito vectors as part of control programs.